Twenty‐years experience with de novo metastatic breast cancer. Issue 6 (23rd March 2015) - Cortesi, Laura; Toss, Angela; Cirilli, Claudia; Marcheselli, Luigi; Braghiroli, Barbara; Sebastiani, Federica; Federico, Massimo
<x xml:space="preserve">Abstract</x> Although new treatments have been widely studied to improve the survival of patients with metastatic breast cancer (BC), prognosis continues to be poor with an average survival time no longer than 3 years. We carried on a population‐based study with the purpose of evaluating the outcome of metastatic breast cancer in the province of Modena from 1990 to 2009. We examined the Modena Cancer Registry and evaluated the 5‐year overall survival (OS) of women diagnosed with a de novo metastatic breast cancer between 1990 and 2009, defining 5 periods of 4 years each. After a median follow‐up time of 29 months, the 5‐year OS was 11% for years 1990–1993, 15% for years 1994–1997, 12% for years 1998–2001, 20% for years 2002–2005 and 29% for years 2006–2009 (p = 0.012). Overall, although no OS differences were noted in the first decade analyzed, a real advantage has been shown in the last two cohorts. In a multivariate analysis, the 5‐year OS was significantly increased only for hormone receptor positive and HER2+ tumors, whereas chemotherapy treatments were not significant independent predictors of survival in "de novo" metastatic BC (p = 0.08). Our analysis confirms that the prognosis of de novo metastatic breast cancer has improved overtime, particularly in the last decade. Trastuzumab, LH‐RH analogues and aromatase inhibitors have determined a significant clinical benefit and cost‐effectiveness in metastatic breast cancer treatment.